Building Peace on the Ruins of Genocide in Iraq: A Socio-Religious Study - Ahmed, Asst. Prof. Dr. Mahdi Qadir Ahmed; Ahmad, Asst. Prof. Dr. Muhammad Abdullah Ahmad (Sulaimani Journal for Humanities, 2024)
This research, employing an inductive-analytical approach, addresses the topic of peacebuilding as a human and social value and a tenet of the Abrahamic religions. Our aim is to cultivate a culture of peace in the Kurdistan Region and Iraq, building upon the ruins of the genocidal campaigns perpetrated against the Kurdish people by the defunct Ba'athist regime. Drawing upon religious teachings, sacred texts, and sociological theories, we hope to resolve the complex relationship between Baghdad and the Kurdistan Region. The significance of this research lies in its focus on peacebuilding following chronic internal and regional conflicts in Iraq. The first section clarifies the concepts of construction, peace, and genocide. The second section sheds light on the steps involved in peacebuilding and the process of rehabilitating Iraqi and Kurdish society. This includes addressing the divisions and closing the gaps through which evil emerges, as well as the steps for peacebuilding through national reconciliation, religious values, reconstruction, compensation for victims, achieving social justice, and fostering responsible human awareness through media and education. The final section addresses building bridges of understanding and shields against division by drafting a national constitution, prosecuting perpetrators of genocide, preventing hate speech, developing democracy, and strengthening institutions with the help of dedicated individuals. This is all in pursuit of lasting peace and a brighter future within a shared environment that thrives on dialogue and equality.
Keywords: Kurdish peacebuilding; genocide; religion; social issues